2011
DOI: 10.4103/2229-4708.81082
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on codeine

Abstract: Alleviation of pain is a major objective in medicine to increase the quality of life. Analgesics are agents that relieve pain by elevating the pain threshold without disturbing consciousness or altering other sensory modalities. Opium is an isoquinoline alkaloid obtained from poppy plant Papaver somniferum (Papaveraceae). Codeine is an alkaloid prepared from opium or morphine by methylation. Codeine is used as a central analgesic, sedative, hypontic, antinonciceptive, antiperistaltic, and is also recommended i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Codeine is an alkaloid prepared from opium poppy ( Papaver somniferum ) by methylation. Heroin produced from opium often contains small amounts of codeine as an impurity [ 15 , 16 ]. Some research suggests that some commercial morphine sulfate preparations may also contain codeine, while other researchers have suggested that codeine is a minor metabolite of morphine sulfate in humans [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Codeine is an alkaloid prepared from opium poppy ( Papaver somniferum ) by methylation. Heroin produced from opium often contains small amounts of codeine as an impurity [ 15 , 16 ]. Some research suggests that some commercial morphine sulfate preparations may also contain codeine, while other researchers have suggested that codeine is a minor metabolite of morphine sulfate in humans [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heroin produced from opium often contains small amounts of codeine as an impurity [ 15 , 16 ]. Some research suggests that some commercial morphine sulfate preparations may also contain codeine, while other researchers have suggested that codeine is a minor metabolite of morphine sulfate in humans [ 14 16 ]. When a morphine to codeine ratio of greater than one is encountered, additional toxicological testing for 6-AM may be all that is needed to discern a case of heroin use [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Codeine is metabolised to morphine in animal body. [ 8 ] Thebaine Papaver somniferum Opiate alkaloid Similar mode of action to morphine. Codeine is metabolised to morphine in animal body.…”
Section: Plant-based Biomolecules With Antiviral Activitiesmentioning
confidence: 99%
“…. " 19 Some litigants even addressed the court about racial biases. One of the few women of color who counter-sued for divorce, Rose Legge, argued with the judge in her trial, complaining that the jury "are white men and they ought not to judge on flimsy evidence."…”
Section: Did Race Matter?mentioning
confidence: 99%